Tobacco and Alcohol Use Among Youth in Low and Middle Income Countries: A Multi-Country Analysis on the Influence of Structural and Micro-Level Factors. (23rd February 2019) - Mutumba, Massy; Schulenberg, John E.
Abstract: Background: The transition from adolescence to adulthood is a critical life phase as it is during this period that substance use and disorders typically emerge and escalate. Globally, few studies have examined the prevalence and correlates of alcohol and tobacco use among youth (ages 15–24). This study seeks to bridge this gap by assessing the influence of structural and micro-level factors on tobacco and alcohol use among youth in Low- and Middle-income countries (LMICs). Methods: Data are drawn from the Multiple Indicator Cluster Surveys (MICS) conducted in 29 countries or regions in Eastern Europe, Latin America, Asia and Africa between 2010 and 2015. Analyses focus on lifetime prevalence and age of onset for tobacco and alcohol use. Results: Descriptive analyses highlight regional variations in the prevalence and age of onset of tobacco and alcohol use: tobacco use is more concentrated among youth in Eastern Europe but alcohol use is generalized across the regions. Using multi-level analyses, we find statistically significant main effects for age, gender, educational attainment, rural residence, marital status and exposure to mass media on tobacco and alcohol use outcomes as well as interaction effects for age, gender and education on tobacco and alcohol use outcomes. Conclusions/importance: These findings highlight the need for structural interventions to control tobacco social marketing, and for gender considerations in tobacco and alcohol use prevention programs and policies.